Taxonomic study of the genus Diolcogaster Ashmead (Hymenoptera, Braconidae, Microgastrinae) from Borneo with the description of four new species - Geng Lu; Shiqi Chen; Yaoyue Lei; Mengqi Wen; Zhen Liu; Mostafa Ghafouri-Moghaddam; Andrew Polaszek (PLoS ONE, 2025)
Taxonomic studies of Microgastrinae (Hymenoptera: Braconidae) are seldom conducted on material from Borneo, despite its being widely recognized as one of the world’s biodiversity hotspots. As part of our preliminary studies on the braconids from this island in the Natural History Museum (UK) collection, we describe and illustrate four new species of Diolcogaster Ashmead: D. dolichogaster Liu & Polaszek, sp. nov., D. flavicoxa Liu & Polaszek, sp. nov., D. hamus Liu & Polaszek, sp. nov., and D. parallela Liu & Polaszek, sp. nov. Two previously described species, D. eclectes (Nixon) and D. urios (Nixon), are redescribed and illustrated. The species examined in this study are classified into two distinct groups, the basimacula–group (D. dolichogaster, D. eclectes, and D. hamus) and the xanthaspis–group (D. flavicoxa, D. parallela and D. urios). Additionally, we provide an identification key to the six Diolcogaster species from Borneo, with a distribution map. A concise discussion of the Diolcogaster species–groups is provided.